Profile of a patient with non-ST segment elevation myocardial infarction in actual clinical practice - V. V. Ryabov; A. E. Gombozhapova; S. V. Demyanov (Российский кардиологический журнал)
Aim. To describe profile of a modern portrait with non-ST-segment elevation myocardial infarction (non-STEMI) through a comprehensive analysis of the Emergency Cardiology Unit (ECU) practice, which discharge a function of a regional vascular centre.Material and methods. To describe the non-STEMI trends of the last decade, we analysed the annual reports on ECU work. The main analysis included patients with a documented non-STEMI treated in 2019 (n=221). We used information from the department database. A Microsoft Excel software was used to create the database. The base has been filled in by the ECU head in real time since 2009. Statistical data processing was performed using the Statistica 10,0 software package. The methods of descriptive statistics and Yates-corrected chi-square test were used.Results. The following clinical and demographic trends of the last decade were revealed: an increase in the number of patients with non-STEMI, proportion of male patients, mean age of patients, proportion of patients with MI with non-obstructive coronary artery disease; no decrease in in-hospital mortality, despite the introduction of modern guidelines, pharmacological and invasive treatment of non-STEMI. In 2019, the proportion of male patients and patients 75 years and older was 62,4% and 32%, respectively. The mean age of patients was 64,6±13,0 years. Clopidogrel was the predominant P2Y12 receptor blockers (56,1%). A total of 176 patients (79,6%) underwent the invasive procedures. Endovascular myocardial revascularization was performed in 97 patients (43,9%), while in the group over 75 years old — in 16 (7%) patients. The leading causes for absence of myocardial revascularization were chronic kidney disease (4,6%), severe coronary artery disease (6,3%), “borderline” (50-60%) coronary artery stenosis. The overall in-hospital mortality rate was 9,0%, while in the group of patients over 75 years old — 19,7%. Mortality rates did not differ in patients with and without myocardial revascularization (p=0,2). However, the incidence of pulmonary oedema was higher in the conservative treatment group (p=0,04).Conclusion. Treatment of patients 75 years and older remains the main barrier in management of patients with non-STEMI. We observe the treatment-risk paradox, which consists in choosing a less aggressive treatment strategy in the group of the most high-risk patients. Other relevant aspects in the management of non-STEMI patients are the selection of a method for myocardial revascularization in multivessel coronary artery disease, assessment of the hemodynamic significance of coronary artery stenosis, and patients with non-obstructive coronary artery disease.